Positive Externality, Increasing Returns, and the Rise in Cybercrimes - Kshetri, Nir B. (Communications of the ACM, 2009)
The meteoric rise in cybercrime has been an issue of pressing concern to our society. According to Federal Bureau of Investigation (FBI), nine out of 10 U.S. companies experienced computer security incidents in 2005 which led to a loss of $67.2 billion. A survey conducted by IBM found that U.S. businesses worry more about cybercrimes than about physical crimes. Internet-related frauds accounted for 46% of consumer complaints made to the Federal Trade Commission (FTC) in 2005. Total losses of Internet fraud victims reporting to FTC increased from $205 million in 2003 to $336 million in 2005. In a July 2007 interview with USA Today, McAfee CEO reported that his company received 3,000-5,000 threat submissions per day from customers and 10% of them were new